2007
DOI: 10.1080/10976640701544589
|View full text |Cite
|
Sign up to set email alerts
|

Relative Role of NT-pro BNP and Cardiac Troponin T at 96 hours for Estimation of Infarct Size and Left Ventricular Function After Acute Myocardial Infarction

Abstract: A single NT-pro BNP and cTnT value at 96 hours after onset of symptoms proved useful for estimation of LV-EF and infarct size. In direct comparison, NT-pro BNP disclosed a better performance for estimation of LV-EF whereas cTnT was superior for assessment of infarct mass and relative infarct size, suggesting an implementation of a dual marker strategy for diagnostic and prognostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 33 publications
3
17
2
1
Order By: Relevance
“…The serum concentration of cTnT in this plateau phase might be a more robust estimate for infarct size [10]. Recently, it was shown that a single value of cTnT 72–96 h after onset of acute STEMI provided an accurate estimate of infarct size determined by magnetic resonance imaging in the acute phase [11,12,13]. However, the data so far are limited, as very few patients were included in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The serum concentration of cTnT in this plateau phase might be a more robust estimate for infarct size [10]. Recently, it was shown that a single value of cTnT 72–96 h after onset of acute STEMI provided an accurate estimate of infarct size determined by magnetic resonance imaging in the acute phase [11,12,13]. However, the data so far are limited, as very few patients were included in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cochet et al (2004) detected the MI size with MRPI and NT-proBNP plasma levels in 84 AMI patients, and found that the NT-proBNP plasma concentration was correlated with MI size (P < 0.01) and LVEF (P < 0.01). Steen et al (2007) found that NT-proBNP and troponin had important value in the evaluation of LVEF and MI size. Bruder et al (2010) reported that in 41 accurate ST stage increase patients, NT-proBNP was correlated with MI size (r = 0.74, P < 0.01), which was stronger than its relationship with LVEF (r = -0.47, P = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to assign upper and lower limits to exclude or diagnose disease and, consequently, difficult to use BNP levels as a routine test, be it for diagnostic, prognostic, or monitoring purposes. Work performed to test the efficiency of combining BNP and cTn to detect and monitor IHD yielded better sensitivity and specificity (94,95), strengthening the argument for a combinatorial approach to biomarker use for clinical cardiovascular diseases.…”
Section: Fig 3 Release Profiles Of Markers Of Myocardial Injury (Admentioning
confidence: 99%